Recent Applications of Nanomaterials in Prosthodontics. (19th May 2015) - Wang, Wei; Liao, Susan; Zhu, Yuhe; Liu, Ming; Zhao, Qian; Fu, Yating
Abstract : In recent years, lots of researches have been launched on nanomaterials for biomedical applications. It has been shown that the performances of many biomaterials used in prosthodontics have been significantly enhanced after their scales were reduced by nanotechnology, from micron-size into nanosize. On the other hand, many nanocomposites composed of nanomaterials and traditional metals, ceramics, resin, or other matrix materials have been widely used in prosthodontics because their properties, such as modulus elasticity, surface hardness, polymerization shrinkage, and filler loading, were significantly increased after the addition of the nanomaterials. In this paper, the latest research progress on the applications of nanometals, nanoceramic materials, nanoresin materials, and other nanomaterials in prosthodontics was reviewed, which not only gives a detailed description of the new related investigations, but also hopefully provides important elicitation for future researches in this field.